Evaluation of Fungal Bioagents against Meloidogyne graminicola (Indian Journal of Nematology, 2024)
An in vitro experiment was conducted to study the efficacy of culture filtrates (CFs) of native fungal bioagents viz.,Trichoderma viride, T. harzianum, Pochonia chlamydosporia and Purpureocillium lilacinum on the mortality of second-stage juveniles (J2) of rice root-knot nematode, Meloidogyne graminicola. The CFs of these bioagents were effective in causing mortality of J2; the efficacy increased with the concentration of CFs and times of exposure. CF of T. viride was most effective, hence, it was selected for further study on its efficacy against M. graminicola under pot conditions. T. viride was applied as a seed treatment, soil application and both. Carbofuran was used as a chemical check. T. viride when applied together as seed treatment and soil application significantlyimproved plant growth parameters of rice and reduced nematode multiplication, as compared to when they were applied singly.Further, the defense-related enzymes showed an increase in the activities of peroxidase (PO), polyphenol oxidase (PPO), phenylalanine ammonia lyase (PAL), and total phenol content in the roots of rice post-treatment. The maximum activities of PO, PPO, PAL and total phenol content were recorded in the rice roots treated with T. viride when applied together as seed treatmentand soil application